Surah Al Mujadalah Translation and Discourse Learning in Higher Education: A Systemic Functional Perspective - Naila Rajiha (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
The main topic in this study is the system of transitivity and modality translation of Al-Quran Al-Mujadalah, and its relevance to the context of learning in higher education, with the goals of 1) determining the system of transitivity and modality, and 2) knowing the type of process and modalities that dominates and determines the relevance of the research on learning discourse in college. The method employed is a qualitative descriptive theory, which is based on Systemic Functional Linguistics. Documentation and records were used to collect data. The data was analyzed using the clause identification method, and the data were analyzed using the described method. According to the findings, the transitivity system as Al-Mujadalah verses 11 is process materials 4 (67 percent), relational identification process as many as 1 (16 percent), behavioral process 1 (16 percent). The shapes of modalities are probability, obligation, and usuality. The dominant of transitivity is a material process and the dominant modality is an obligation. In the context of higher education, discourse learning is not only about analyzing the text i.e Quran but also about the urgency of the message based on that surah translation.